THE EXPERIENCE OF TEMS NURSES IN HANDLING TRAFFIC ACCIDENT VICTIMS IN RSUD DR. ISKAK TULUNGAGUNG - Maria Wisnu Kanita; Retty Ratnawati; Retno Lestari (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2018)
Emergency Medical Services (EMS) in Indonesia has not been developed comprehensively. EMS service that has been running is in RSUD dr. Iskak Tulungagung named Tulungagung Emergency Medical Services (TEMS) with the most incident call are traffic accidents. Nurses experienced some obstacles when handling the traffic accident victims which made it cannot be done optimally. This study aims to explore the experience of nurses in conducting EMS on the handling of traffic accident victims in RSUD dr. Iskak Tulungagung. The research was using qualitative method with interpretive phenomenology approach by using data analysis process based on Interpretative Phenomenological Analysis (IPA). Nine themes were obtained from 9 participants: 1) Assuming the importance of providing the best treatment, 2) Encourage team cohesiveness to facilitate handling, 3) Feel the contradictions in the self when dealing with victims, 4) Feeling the emergence of spirit in self, 5) Serving with wholeheartedly embodied with the priority of the victim, 6) Experiencing poor acceptance from the community, 7) Experiencing the limited, 8) Craving accurate service by a competent team, and 9) Feeling increasing public trust who knowing TEMS. Establishing EMS from the beginning to the current process, based on the awareness of the nurse and the relevant parties regarding the appropriate and best handling of traffic accident victims to achieve patient safety. Regular evaluation is needed from all related parties and education for community for handling of traffic accident victims in EMS service so it can be given maximally by the nurse.